Implementation methodology for android application development - Babu, Bulli; Naveen, Jada; Rajinikanth, Kondaveeti; Sai Ram Krishna, Pothagani (International Journal of Engineering and Technology, 2018)
As the tuning flow of theÂ Â modern world of technology, the mobile APKsÂ are tremendous extracting segment of the globalization smart marketing technology. smart APKs applications are involving to a meteor pace to rise level of n utilizes and users a rich in report.Â AS on the paper , Android Platform for the developing the mobile applications. Firstly, we are Here To explain about theÂ develop the android application as by our learnt knowledge we have created the application According to my college Website as the Business users pattern mode. Majorly we have to describe in this app is website users have to use the systems to check the recent updates and announcements and other regarding the things about relatedÂ to the academic details. for that sake we have created the application by the tutorial knowledge and basics. This app can used as same as website with as the single tap in the smart mobile. As we are tried the app as best asÂ possible manner in our way of our knowledge. This knowledge and creation of our works we have learnt lots things .I acquired good progress report in the creation of the application.